The Potential Impact of Blockchain Technology on Audit Practice - Brender, Nathalie; Gauthier, Marion; Morin, Jean-Henry; Salihi, Arbër (Journal of Strategic Innovation and Sustainability, 2019)
In today’s debate on the potential disruptive effects of blockchain, audit and control professions are rarely in the spotlight although applications such as smart contracts and distributed ledgers could significantly impact them. We conducted a study based on the grounded theory to understand how auditors in Switzerland anticipate the impacts of blockchain on their activities. Based on our findings, three hypotheses have emerged. First, the potential effect of blockchain on the profession is not fully anticipated. Second, the profession will go through a paradigm shift in two ways: become more IT oriented and forward looking. Finally, the profile of the auditors will change.